2004
DOI: 10.1002/macp.200400192
|View full text |Cite
|
Sign up to set email alerts
|

Novel Possibilities by Cationic Ring‐Opening Polymerisation of Cyclodextrin Derivatives: Preparation of a Copolymer Bearing Block‐Like Sequences of Tri‐O‐methylglucosyl Units

Abstract: Summary: Equimolar mixtures of O‐permethylated and O‐perdeuteromethylated cyclodextrins were submitted to cationic ring‐opening polymerisation (CROP) with Et3OPF6 or BF3 · Et2O as initiator in dichloromethane. Reaction started after an incubation time and yielded a polymeric product, which was partially degraded again during competing chain transfer reaction. Average block length was determined by ESI‐MS after partial methanolysis and was found to be close to the theoretical value of 14 for β‐cyclodextrin in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…In preliminary investigations of Suzuki [Suzuki et al 2001] and our laboratory [Adden et al 2004], a lag phase of the polymerisation reaction has been observed. This has also been reported for CROP of simple acetals as 1,3-dioxolane.…”
Section: H Nmr Spectroscopic Studies Of the Course Of Polymerisationmentioning
confidence: 98%
See 4 more Smart Citations
“…In preliminary investigations of Suzuki [Suzuki et al 2001] and our laboratory [Adden et al 2004], a lag phase of the polymerisation reaction has been observed. This has also been reported for CROP of simple acetals as 1,3-dioxolane.…”
Section: H Nmr Spectroscopic Studies Of the Course Of Polymerisationmentioning
confidence: 98%
“…Disaccharides obtained from random methanolysis of the polymeric product are analysed by ESI-MS [Adden et al 2004 …”
Section: Average Block Length (Bl)mentioning
confidence: 99%
See 3 more Smart Citations